PHARMACOLOGICAL APPROACH IN EXERCISE-INDUCED ASTHMA - Biljana Vitošević; Radoslav Mitić; Iva Nikolić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Exercise-induced asthma is a transient airflow obstruction, which occurs after the strenuous exercise. It is a complex pathophysiological phenomenon, present in all levels of exercise, from children to professional athletes, so the therapy is specific and individual. Pharmacological therapy involves short-acting β2 adrenergic agonists, as well as long-acting, mast cell-stabilizing agents, leukotriene receptor antagonists, muscarinic receptor antagonists and inhaled corticosteroids. Although the practice of application only one type of medication, recent literature data indicate a better effect of combined treatment. Appropriate medical prophylaxis and education of athletes plays an important role in the treatment of exercise-induced asthma, because in this way the incidence of bronchoconstriction decrease, reduce symptoms and provides comfortable acting in sport.